Lumalindaw. [anthology].
Lumalindaw, the hero of the Ga'dang, was the son of Chief Lumalibac of Nabbobawan and his wife Caricagwat. He was an extraordinary being. In a few days he grew into a strong young man with a voice so loud that if he shouted at a flying bird, it would drop instantly in front of him, and if he shouted at a coconut tree, its fruits would fall.
Found in: Philippine Folk Literature : The Epics. (GR 325 P48 2001 v.8)
Keywords: Literature-Collections.